Extrinsic Rashba spin–orbit coupling effect on silicene spin polarized field effect transistors. (27th February 2017) - Pournaghavi, Nezhat; Esmaeilzadeh, Mahdi; Abrishamifar, Adib; Ahmadi, Somaieh
Abstract: Regarding the spin field effect transistor (spin FET) challenges such as mismatch effect in spin injection and insufficient spin life time, we propose a silicene based device which can be a promising candidate to overcome some of those problems. Using non-equilibrium Green's function method, we investigate the spin-dependent conductance in a zigzag silicene nanoribbon connected to two magnetized leads which are supposed to be either in parallel or anti-parallel configurations. For both configurations, a controllable spin current can be obtained when the Rashba effect is present; thus, we can have a spin filter device. In addition, for anti-parallel configuration, in the absence of Rashba effect, there is an intrinsic energy gap in the system (OFF-state); while, in the presence of Rashba effect, electrons with flipped spin can pass through the channel and make the ON-state. The current voltage ( I – V ) characteristics which can be tuned by changing the gate voltage or Rashba strength, are studied. More importantly, reducing the mismatch conductivity as well as energy consumption make the silicene based spin FET more efficient relative to the spin FET based on two-dimensional electron gas proposed by Datta and Das. Also, we show that, at the same conditions, the current and I o n / I o f f ratio of silicene based spin FET are significantly greater than that of the graphene based one.